2010
DOI: 10.4103/0019-509x.73561
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma esophagus: A rare primary malignancy for ocular metastasis

Abstract: Carcinoma esophagus: A rare primary malignancy for ocular metastasisSir, Carcinoma of esophagus is a devastating disease because of its effects on nutrition in the patients. Half of the cancers are unresectable and metastatic at presentation, and curative success in dealing with cancer is less than 10%. Here, we report an unusual case of esophageal cancer with ocular metastasis. Figure 5: CT scan image showing a soft tissue lesion measuring 1.0 × 0.5 cm at right fovea.Figure 4: PET scan image showing a hyperme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…To the best of our knowledge, there are two other reported cases of metastatic esophageal cancer to the retina. [ 4 , 6 ] The first case is for a 56-year-old male patient who presented at Wills Eye Hospital, the interval from primary cancer diagnosis to retinal metastasis was 26 months, the patient was only observed due to poor prognosis, and he died after a year. [ 4 ] The second case was described by Pal et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are two other reported cases of metastatic esophageal cancer to the retina. [ 4 , 6 ] The first case is for a 56-year-old male patient who presented at Wills Eye Hospital, the interval from primary cancer diagnosis to retinal metastasis was 26 months, the patient was only observed due to poor prognosis, and he died after a year. [ 4 ] The second case was described by Pal et al .…”
Section: Discussionmentioning
confidence: 99%
“…for a 68-year-old patient, who presented with right eye chorioretinal metastasis 2 months following diagnosis with esophageal carcinoma; he was managed by a combination of local radiotherapy and palliative chemotherapy. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Among the primary cancers most commonly associated with uveal tract metastases, breast cancer ranks first (47%), followed by lung (21%), prostate, and gastrointestinal tumors, among which the most frequent site is the stomach followed by the colon, whereas cases of esophageal cancer as the primary cancer are exceedingly rare. Since Mullaney et al [9] described the first case of ESCC with choroidal metastasis in 1970, only 6 more cases have been reported in the literature [5,10]. Common presentations of ocular metastasis include a decrease in visual acuity, scotoma, black spots appearing, pain, and secondary glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…The reported median survival after the diagnosis of symptomatic choroidal metastasis ranges from 4.3 to 7.4 months [5]; however, in most cases, the patients' general condition is so poor that curative therapy cannot be performed by the time the ocular lesion is detected. Pal et al [10] reported on the only known case of ESCC with chorio‐retinal metastasis; this patient reportedly received palliative chemotherapy and radiotherapy, but there was no information regarding the patient's survival. The short life expectancy of patients with advanced/metastatic ESCC may be one of the reasons for the scarcity of reports on the topic.…”
Section: Discussionmentioning
confidence: 99%